Methods to measure blood flow and vascular reactivity in the retina - Böhm, Elsa Wilma; Pfeiffer, Norbert; Wagner, Felix Mathias; Gericke, Adrian (Frontiers in Medicine, 2023)
Disturbances of retinal perfusion are involved in the onset and maintenance of several ocular diseases, including diabetic retinopathy, glaucoma and retinal vascular occlusion. Hence, knowledge on vascular anatomy and function is highly relevant for basic research studies and for clinical judgement and treatment. The retinal vasculature is composed of the superficial, intermediate and deep vascular layer. Detection of changes in blood flow and vascular diameter especially in smaller vessels is essential to understand and to analyze vascular diseases. Several methods to evaluate blood flow regulation in the retina have been described so far, but no gold standard has been established. For highly reliable measurements of retinal blood flow, exact determination of vessel diameter is necessary. Several measurement methods have already been reported in humans. But for further analysis of retinal vascular diseases, studies in laboratory animals, including genetically modified mice, are important. As for mice, the small vessel size is challenging requiring devices with high optic resolution. In this review, we recapitulate different methods for retinal blood flow and vessel diameter measurement. Moreover, clinical studies in humans and in experimental animals are described.